ANALYSIS OF NURSING CLINICAL PRACTICES FOR PREVENTING DECUBITUS WOUNDS IN STROKE PATIENTS USING SKIN BARRIER PETROLEUM JELLY - Riskatrianti, Riskatrianti; Siti Khoirun Muflihatin; Slamet Purnomo; Fitroh Asryadi (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Non-hemorrhagic stroke patients often experience limited mobility and prolonged bed rest during hospitalization, increasing the risk of developing pressure ulcers due to continuous pressure on bony prominences. This condition can be exacerbated by other factors such as sensory impairment, skin moisture, and inadequate nutritional status. Pressure ulcers are a common complication in immobilized patients and can lead to increased length of hospital stay, increased risk of infection, and higher healthcare costs. Therefore, preventive measures are needed through appropriate nursing practices, one of which is skin care using a skin barrier to maintain skin integrity. Petroleum jelly is known to have occlusive properties that can maintain skin moisture and protect it from friction and irritation. This analysis of nursing clinical practice aims to analyze the application of skin care using petroleum jelly as a skin barrier to prevent the risk of pressure ulcers in non-hemorrhagic stroke patients in the Elang III Ward of Aji Muhammad Parikesit General Hospital, Tenggarong. The method used was clinical practice analysis with a comprehensive nursing care approach that includes assessment, establishing a nursing diagnosis, planning, implementation, and evaluation. The results of the analysis showed that routine application of petroleum jelly to high-risk areas can maintain skin integrity, reduce excess moisture, and reduce the potential for pressure ulcers. The conclusion of this study shows that the use of petroleum jelly as a skin barrier is a simple, safe, and effective nursing intervention in preventing the risk of pressure ulcers in non-hemorrhagic stroke patients and has the potential to improve the quality of nursing care.